McKinsey quarterly : How to grow again.. (McKinsey Quarterly. Number 2, 2011., 2011)
1. How much emphasis is placed on emerging markets? How granular is the growth strategy? How far can the boundaries of the business model be pushed? How realistic is the growth strategy? Also Starbuck's quest for health growth - The world's new growth frontier - Is your emerging-market strategy local enough - Seven steps to better brainstorming - Sparking creativity in teams - Growth in a captial constrained world - Organizational health : the ultimate competitive advantage.